Land cover and air pollution are associated with asthma hospitalisations: A cross-sectional study. (December 2017) - Alcock, Ian; White, Mathew; Cherrie, Mark; Wheeler, Benedict; Taylor, Jonathon; McInnes, Rachel; Otte im Kampe, Eveline; Vardoulakis, Sotiris; Sarran, Christophe; Soyiri, Ireneous; Fleming, Lora
Abstract: Background: There is increasing policy interest in the potential for vegetation in urban areas to mitigate harmful effects of air pollution on respiratory health. We aimed to quantify relationships between tree and green space density and asthma-related hospitalisations, and explore how these varied with exposure to background air pollution concentrations. Methods: Population standardised asthma hospitalisation rates (1997–2012) for 26, 455 urban residential areas of England were merged with area-level data on vegetation and background air pollutant concentrations. We fitted negative binomial regression models using maximum likelihood estimation to obtain estimates of asthma-vegetation relationships at different levels of pollutant exposure. Results: Green space and gardens were associated with reductions in asthma hospitalisation when pollutant exposures were lower but had no significant association when pollutant exposures were higher. In contrast, tree density was associated with reduced asthma hospitalisation when pollutant exposures were higher but had no significant association when pollutant exposures were lower. Conclusions: We found differential effects of natural environments at high and low background pollutant concentrations. These findings can provide evidence for urban planning decisions which aim to leverage health co-benefits from environmental improvements. Highlights: Natural environments in urban areas were associated with less asthma hospitalisation. These associations varied by coexisting background air pollution concentration. Green space/gardens were associated with less asthma when NO2 /PM2.5 was lower. Urban trees were associated with less asthma when NO2 /PM2.5 was higher.